Fabrication, characterization and electrochemical performance of single strand carbon fiber prepared by catalytic chemical vapor decomposition method - Joshi, Vrushali S.; Gokhale, Suresh P.; Patil, Kashinath R.; Haram, Santosh K. (Electrochimica Acta, 2010)
Preparation, fabrication and voltammetric characterizations of a single strand of carbon fiber (SSCF) electrode and their potential applications for biosensor are presented. SSCFs of diameter ca. 10 +/- 2 mu m and few millimeters in length are prepared by catalytic chemical vapor decomposition (CCVD) method. Voltammetry with potassium ferricyanide. alpha-methylferrocene methanol and hexaammineruthenium(III) chloride on SSCF electrode are used as bench marks to validate the electrode properties. Quasi-steady state voltammograms obtained were fitted into a cylindrical diffusion model From which, the standard rate constant (k(0)) and electron transfer coefficient (alpha) are obtained. The use of SSCF electrode is demonstrated for the voltammetric detection of the micromolar quantity of dopamine in the presence of large excess (ca. 200 times) of ascorbic acid, without any fouling of electrode surface. The kinetics of electron transfer are investigated. (C) 2009 Elsevier Ltd All rights reserved.
Keywords: alpha-Methylferrocene methanol; Ascorbic acid; Catalytic chemical vapor decomposition (CCVD); Cylindrical diffusion; dopamine; Hexaammineruthenium(III) chloride; Single strand carbon fiber (SSCF) electrode